The University Idea: Retrospection, Vertions and Prospects - A. G. Kislov; O. V. Shmurygina (Russian State Vocational Pedagogical University, 2015)
The paper explores the main versions of the university idea, mission and essence in the context of different historical eras. The authors analyze the philosophical and pedagogical heritage of foreign and Russian thinkers, and trace the main evolutionary stages of higher school development A great variety of university ideas comes from the precise historical peculiari- ties and experiences; though, all the existing versions are associated with ideal- istic (platonic, essentialist) positions. However, the authors highlight the his- torical relativistic approach regarding the higher school as flexible and adapting to the requirements of the relating era, and holding that declaration of the uni- versity idea changes according to the altering society demands. In conclusion, it is emphasized that the most prospective direction for overcoming the higher educational crisis involves considering the society demands and constructing and reconstructing a functional response of the higher school to those de- mands. The research findings can be applied to further studies aimed at ana- lyzing the higher school position and predicting its future.